Are our patients waiting too long for cardiac surgery?. (25th November 2020) - Menezes Fernandes, R; Mota, T.F; Bispo, J.S; Costa, H; Bento, D; Marques, N; Mimoso, J; Jesus, I
Abstract: Introduction: Recommended pre-established waiting periods in patients referred for cardiac surgery aim to improve clinical outcomes. Purpose: To determine the prognostic impact of the delay until cardiac surgery. Methods: We conducted a retrospective study encompassing patients referred to cardiac surgery from a Cardiology Department, since January 2016 to December 2018. Clinical characteristics, diagnostic studies and follow-up were analysed. Primary endpoints were global mortality and re-hospitalization rates at follow-up. Independent predictors of clinical outcomes were identified through a binary logistic regression analysis, considering p=0, 05. Results: A total of 591 patients were included, with 71, 1% male predominance and a mean age of 68, 6±11, 36 years old. 55, 2% of patients had severe valvular disease (aortic – 38, 6%, mitral – 9, 6%, mixed valvular disease – 2, 9%), and 37, 1% had surgical coronary artery disease. The mean left ventricle ejection fraction was 56, 1% ± 12, 2% and the mean Euroscore II was 3, 7%. 120 patients (20, 3%) required more than one type of surgical intervention. 360 patients (60, 9%) were referred to elective procedures, with a mean waiting time of 129, 4 days and only 29, 2% of them were operated in a 6-week period. The remaining 39, 1% of patients needed urgent/emergent surgery, and the mean time until the intervention was 27, 2 days (70, 1% operated in 2-weeks). Mean waiting time was higher for valvular patients comparing with coronary patients (110, 7 vs 48 days; p<0, 001). 9, 8% and 4, 6% of patients were re-hospitalized or died while waiting for surgery, respectively. In a median follow-up of 520 days since the surgical referral, 25, 5% of patients were re-hospitalized and 13, 7% died. Waiting time was an independent predictor of global mortality (p=0, 018), as well as arterial hypertension (p=0, 002), severe valvular disease (p<0, 001) and higher Euroscore II values (p=0, 023). Waiting for surgery in an out-patient setting (p=0, 011) and higher Euroscore II values (p=0, 002) were independent predictors of re-hospitalization. Conclusion: In our study, waiting time until surgery was an independent predictor of global mortality. Efforts should be made to enable referral surgical centres to timely respond to the needs of the population, considering the impact that delaying the appropriate treatment can have on the survival of these patients. Funding Acknowledgement: Type of funding source: None